Far-Field Impacts of a Super Typhoon on Upper Ocean Phytoplankton Dynamics - Qiu, Guoqiang; Xing, Xiaogang; Chai, Fei; Yan, Xiao-Hai; Liu, Zhiyu; Wang, Haili (Frontiers in Marine Science, 2021)
Super typhoon Rammasun (2014) traveled across the South China Sea on July 16–18. Its far-field impacts on phytoplankton dynamics in the upper ocean were documented by a Biogeochemical-Argo (BGC-Argo) float located 200 km to the left of its track. Both surface chlorophyll-a concentration (Chla) and particulate backscattering coefficient (bbp) were observed to increase substantially within two distinct stages. The initial increase occurred during the passage of the typhoon, and the subsequent increase happened 5 days after the typhoon. In contrast, depth-integrated Chla and bbp in the upper 150 m underwent negligible changes throughout the entire period. The key lies in the fact that surface phytoplankton increases in the far-field region resulted from the physically driven vertical redistribution of particles, rather than from biological alternations. The first increase was attributed to the typhoon-induced strong turbulence which deepened the surface mixed layer, and thus entrained subsurface particles to the surface; the second was due to the post-typhoon adiabatic quasi-geostrophic adjustment of the upper ocean that gradually raised the isopycnals (and thus subsurface particles). These results challenge the prevailing wisdom on typhoon impacts, and thus shed new lights on the nature of the upper ocean responses to typhoons from both physical and biological perspectives.